Umbilical Cord Mesenchymal Stem Cells Ameliorate Kidney Injury in MRL/Ipr Mice Through the TGF-β1 Pathway - Huang, Chunkai; Meng, Mingyao; Li, Shuo; Liu, Shiyuan; Li, Lin; Su, Yanjun; Gao, Hui; He, Shan; Zhao, Yiyi; Zhang, Min; Hou, Zongliu; Wang, Wenju; et al. (Frontiers in Cell and Developmental Biology, 2022)
The therapeutic effects and mechanism of umbilical cord mesenchymal stem cells (UC-MSC) on kidney injury in MRL/Ipr mice were studied. UC-MSC, methylprednisolone (MP), and their combination were used to treat MRL/Ipr mice. The therapeutic effects were evaluated by renal function assessment, and HE, PAS, and Masson staining were carried out on renal tissues and visualized by electron microscopy. Subsequently, podocyte injury was detected by the presence of podocin in renal tissues by immunofluorescence. To further explore the mechanism, serum TGF-β1 was measured, and TGF-β1, p-Smad3, and TRAF6 in the renal tissue were detected by Western blotting. In vitro, TGF-β1 was used to stimulate podocytes, and the podocyte activity and changes in synaptopodin were observed after UC-MSC treatment. Significant improvements in renal function and pathological injury were observed in the UC-MSC group compared to the lupus nephritis (LN) model group. UC-MSC and MP treatment improved podocyte injury in MRL/Ipr mice. Western blot examination showed a significant increase in TGF-β1, p-Smad3, and TRAF6 expression in renal tissues of the LN model group, while significant downregulation of those proteins was observed in the UC-MSC group. After TGF-β1 stimulation in vitro, podocyte activity decreased, and UC-MSC treatment improved podocyte activity and restored synaptopodin expression. UC-MSC therapy could improve the deterioration of renal function and the pathological changes of the renal tissues in MRL/Ipr mice. Our study suggested that UC-MSC may improve kidney injury and podocyte injury in LN mice by inhibiting the TGF-β1 pathway.